Unraveling crop enzymatic browning through integrated omics - Wang, Chunkai; Meng, Lin; Zhang, Guochao; Yang, Xiujun; Pang, Bingwen; Cheng, Junjie; He, Bing; Sun, Fushan (Frontiers in Plant Science, 2024)
Enzymatic browning reactions, triggered by oxidative stress, significantly compromise the quality of harvested crops during postharvest handling. This has profound implications for the agricultural industry. Recent advances have employed a systematic, multi-omics approach to developing antibrowning treatments, thereby enhancing our understanding of the resistance mechanisms in harvested crops. This review illuminates the current multi-omics strategies, including transcriptomic, proteomic, and metabolomic methods, to elucidate the molecular mechanisms underlying browning. These strategies are pivotal for identifying potential metabolic markers or pathways that could mitigate browning in postharvest systems.